Thinking without Heidegger? - Horsthemke, Kai (Forum Pedagogiczne, 2019)
There has been a resurgence of Martin Heidegger’s ideas in recent years, especially within English-language philosophy of education. Yet, there have also been other developments that deserve to be taken seriously, first and foremost the indication that his anti-Semitism informs not only his personal beliefs and political stance but is already rooted in his philosophy, notably his ontology. It is these developments and the context of Heidegger’s philosophy that are examined first, before I return to the purported significance of his ideas for education towards the end of this essay.